2023
DOI: 10.5430/wjel.v13n7p10
|View full text |Cite
|
Sign up to set email alerts
|

Lesson Study Contributions: EFL Teachers' Competences Model in Teaching English at High School 21st-Century Learning Approach

Abstract: The quality of learning relies on the teacher, serving as a critical factor in determining its effectiveness. This study aims to develop a teacher competency model through Lesson Study (LS) activities. Model competence refers to the regulation of Indonesian Ministry of Education and Culture No 6565 in 2020. This study applied the qualitative descriptive research design. It utilized the lesson study approach in developing EFL teacher's professional knowledge competence, professional learning practice competence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…Islamic education teachers face several challenges in implementing the Merdeka Curriculum. First, the challenge faced is teacher competence (Hadi et al, 2023;Jones et al, 2021;Mahmud et al, 2023;Mohammadi Zenouzagh et al, 2023). Merdeka Curriculum requires teachers to have a deep understanding of the subject and the ability to develop innovative learning materials and methods (Looi et al, 2023).…”
Section: Challenges Faced By Islamic Education Teachers In Implementi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Islamic education teachers face several challenges in implementing the Merdeka Curriculum. First, the challenge faced is teacher competence (Hadi et al, 2023;Jones et al, 2021;Mahmud et al, 2023;Mohammadi Zenouzagh et al, 2023). Merdeka Curriculum requires teachers to have a deep understanding of the subject and the ability to develop innovative learning materials and methods (Looi et al, 2023).…”
Section: Challenges Faced By Islamic Education Teachers In Implementi...mentioning
confidence: 99%
“…Previous research has shown that the implementation of the Merdeka Curriculum can foster increased motivation (Aliyyah et The Merdeka Curriculum has the potential to inspire teachers to incorporate a wider range of educational approaches (Jonker et al, 2020;Supriyoko et al, 2022), ensuring that students engage in more meaningful learning experiences (Tumin et al, 2020). Moreover, this curriculum has the ability to enhance the overall quality of education within schools (Aliyyah et al, 2023;Mahmud et al, 2023;Purwasih et al, 2021). By granting educators the freedom to tailor their teaching methods according to the unique needs and interests of their students, the Merdeka Curriculum unlocks a world of possibilities (Zaini & Wahib, 2022).…”
Section: Introductionmentioning
confidence: 99%